Evaluation of Marbofloxacin in Beagle Dogs After Oral Dosing: Preclinical Safety Evaluation and Comparative Pharmacokinetics of Two Different Tablets - Lei, Zhixin; Liu, Qianying; Yang, Bing; Khaliq, Haseeb; Ahmed, Saeed; Fan, Bowen; Cao, Jiyue; He, Qigai (Frontiers in Pharmacology, 2018)
The current study evaluates a tested marbofloxacin tablet (Petsen), in terms of bioavailability and pharmacokinetics in a comparison of the commercialized and standard tablet (Marbocyl) in beagle dogs. Four different bacterial species were selected for the determination of the minimal inhibitory concentration against marbofloxacin. Target animal safety studies were conducted with a wide spectrum of dosages of Petsen. Pharmacokinetics and bioavailability of Petsen were observed after the oral administration of a recommended dosage of 2 mg/kg. The MIC90 of marbofloxacin against Staphylococcus aureus, Escherichia coli, Pasteurella multocida, and Streptococcus were 2.00, 4.00, 0.25, and 0.50 μg/ml respectively. These results showed that the marbofloxacin tablet has an expected antimicrobial activity in vitro. The main parameters of t1/2β, Clb, AUC0-∞, Cmax and Ke were 22.14 h, 0.15 L/h, 13.27 μg.h/ml, 0.95 μg/ml, 0.09 h-1 and 16.47 h, 0.14 L/h, 14.10 μg.h/ml, 0.97 μg/ml, 0.11 h-1 after the orally administrated Petsen and Marbocyl, while no biologically significant changes and toxicological significance have been found by their comparison. These findings indicate that the Petsen had a slow elimination, high bioavailability and kinetically similar to the commercialized Marbocyl. Furthermore, no statistically significant differences were distinguished on the continuous gradient dosages of 2, 6, and 10 mg/kg in the term of the clinical presentation. The present study results displayed that the tested marbofloxacin tablet (Petsen) was safe, with limited toxicity, which was similar to the commercialized tablet (Marbocyl), could provide an alternative marbofloxacin tablet as a veterinary medicine in beagle dogs.